An Integrative Ayurvedic Approach In Management Of Shashtrakruta (Post-Operative) Complicated Gudajacharmakeela Arsha(Anal Warts) – A Rare Case Report: Life Sciences-Ayurveda - Biswas, Dr Shubham; Asutkar, Dr Sheetal; Dasar, Dr Devyani; Parwe, Shweta (International Journal of Life Science and Pharma Research, 2023)
CharmakeelaArsha (Anal warts) are small growths in and around the anal region caused by the human papillomavirus (HPV). The patient, the age 39- years female, came to O.P.D. of shalyatantra complaining of baddhamalapravruti (hard stools), sarakta malapravruti (bleeding per rectum on and off), Guda pradeshi Mamsankura prachiti (feeling of mass at anal region), sashoola malapravruti (pain during and after defecation) since six months. Clinically diagnosed patient as a case of Charmakeelaarsha (anal warts) with internal piles and sentinel tag. Chedana (Excision) of anal warts and Sentinel tag by Agnikarma (electric cautery) was performed with ligation haemorrhoidectomy under spinal anaesthesia. It is challenging to manage post-operative wound healing with simple ointments. So there is a need to intervene in the ayurvedic ointments and treatment of post-operative wounds to heal them faster with no complications. After the operative procedure, the patient was managed with Ayurvedic protocols like laghu ahara, deepana, panchana, Virecheniya dravya, and Vranaropaka ointment for 15 days. The patient was assessed by Subjective and Objective parameters like the Numerical pain Scale, WHO are bleeding Scale, and VranaPariksha based on signs and Symptoms. The patient showed improvement in signs and Symptoms on the 15th Day. After two months of follow-up, the patient recovered well, and no recurrence or complaint was observed. Hence, such a study is more important for better wound healing and pain management. Instead of taking more extended oral therapies or anaesthetic blocks in post-operative management, the short procedure, like the present study, can save time. This case proved the efficacy of ayurvedic management in Shashtrakruta Charmakeela Arsha.